Effects of Agricultural Credit and Microfinance on Expenditure Patterns in Yemen - Asanoy, Adnan (2004)
Poverty is a core problem in the Yemeni economy. About 47 percent of the total population lives below the poverty level. Moreover, the rapidly increasing population causes competition at meeting basic needs. From the macro economic point of view, Yemen also experiences unemployment problem and other socially adverse phenomena that contribute to low GDP. The economy of Yemen is vitally dependent on the growth of the rural economy, too. The majority of the people live in the rural areas. Due to the fact and the present socio-economic structure, the national and economic development of Yemen has been adversely affected. In order to meet the poverty crisis, the government of Yemen reformed its economic policy and undertook a small-scale credit program. Under this reformation, the National Agricultural Bank of Yemen has introduced agricultural credit and microfinance programs in mid 1980's and 1990's respectively. At present, the programs have progressed and could be evaluated for its success towards the aim of reducing poverty. The present study attempts to evaluate the effectiveness of introducing small-scale credit towards better livelihood of the beneficiaries. Using econometric modeling, the study focused on the living standard of the beneficiaries. To examine the effectiveness accurately, a non-beneficiary group was also studied. By comparing two groups of respondents namely, "with credit" and "without credit", the study attempted to portray the effectiveness of the program. The sample size in this study was 540. A total of seven governances were selected for data collection. Simple random sampling procedure was used to select the respondents from the sampling frame. The study used Extended Linear Expenditure System (ELES) to estimate the poverty line and the living standard based on the socio-economic attributes of the respondents. In ELES, a demand system for food and non-food items was used. The impact of credit was measured by incorporating a dummy variable representing the 'with-without' group into the model. The study extended its investigation hrther by carrying out a logistic regression analysis to determine the borrowers' preference between the two programs based on the socio-economic attributes. The dependent variable of the model was dichotomous namely, microfinance or otherwise. 'Otherwise' includes the respondents who preferred agricultural credit. The results showed that there was a significant effect of socio economic variables and other factors on the expenditure of different food and non-food items. Education and family size showed significant contribution to the total expenditure. Dummy 'with-without' credit was found significant, too. This indicated that there was a significant effect of small-scale credit program on the demand of food and non-food items. The standard of living of 'with-credit' group was found higher than that of 'without-credit' group. Logistic regression analysis showed that the respondents preferred microfinance. Income, education and family size were found to significantly determine the preferences for credit. Based on the findings of the study, it is recommended that further extension of credit programs to the other poor governances of Yemen would be able to enhance the socio economic status of the people. Input supports, low interest rate, reformation of repayment structure are required to be reviewed for further development of policy.